Pandemic Pedagogy: Anonymous Peer Workshop for Increased Effectiveness and Inclusivity (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
Peer review workshops are common practices in many writing and composition classrooms, and their benefits have been well-documented. However, complications arise when students arrive to workshops with their own baggage—unconscious biases, enculturated prejudices, and general anxiety about critiquing another’s work. These impediments can negatively affect the classroom atmosphere in general and the value and effectiveness of peer review activities in particular. With COVID-19 causing many universities to move to online-only instruction, an opportunity arose to incorporate anonymity into the writing workshop. This article reviews the drawbacks of traditional, face-to-face writing workshops and the benefits of anonymity for peer review, and shares the nuts and bolts of one successful online, anonymous peer review activity. This article concludes by offering both student-participant feedback and suggestions for activity adoption and improvement of peer reviews.